A ONU e o genocídio de Srebrenica - Silva, Cristiane Barboza Lopes da (2021)
This work aims to analyze the mistakes made during the peacekeeping mission conducted by the United Nations Protection Force (UNPROFOR) in the Bosnian War (1992-1995) that might have made possible the occurrence of a genocide that killed approximately 8,000 men and boys in an area that was under its protection. Our hypothesis was that structural problems of the battalion allied to its pacifying characteristic, with the use of light weapons and without a mandate to use force except for self-defense, would have made it possible for the Bosnian Serbs to take over the city. This explanation proved to be partly adequate, however, the issue is more complex than that, also involving interests of the countries of the UN Security Council and political decision-making disconnected from the reality of the conflict on the ground. It is a bibliographic and descriptive research that explores the academic production related to the theme, as well as documents published about the massacre, aiming to investigate and describe the events that took place in the enclave. To better portray the subject, we summarize the history of the Balkans, the region in which the city is located, and reconstruct the formation of the former Yugoslavia until its fragmentation in the early 1990s, seeking to present the ethnic and cultural multiplicity of the region and how this element was used to generate the hatred that resulted in the first genocide in European lands after the Second World War.